The principle and advantages of Real-time PCR - Konovalova, A.A.; Mashzhan, A.S.; Khodkov, A.V.; Pogossyan, G.P.; Zhumina, A.G.; Oganesyan, R.G. (Fundamental and Experimental Biology, 2016)
The article is devoted to the modern methods of molecular diagnostics — polymerase chain reaction in real time. The components, stages of this reaction, the amplification products visualization techniques and its ad-vantages are also described. The main components of the Real-time PCR are DNA polymerase enzyme, pri-mers, DNA template, fluorescent dye, nucleotides. The advantages of Real-time PCR include direct determination of the presence of pathogens, a high specificity, high sensitivity, universality of the various procedures to identify DNA and RNA, high speed of analysis, the possibility of the diagnostics of acute and latent infections, the possibility of preclinical and retrospective diagnostics, the ability to conduct analysis with minimal sample, the possibility of simultaneous diagnosis of several pathogens or abnormal genes in one, the possibility of research results examining; exclusion of the possibility to the personnel infection. The information about additives and enhancing agents can be included in PCR amplifications to increase yield, specificity and consistency are also given in the article.